2019
DOI: 10.1016/j.jpainsymman.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Fan Therapy for the Treatment of Dyspnea in Adults: A Systematic Review

Abstract: Context. The use of a handheld or electric fan has been proposed as one component of the complex clinical interventions used in the relief of dyspnea; however, there is a lack of consensus regarding its efficacy.Objectives. We performed a systematic review to determine the effectiveness of fan therapy for the treatment of dyspnea. Methods. We searched the Medline, EMBASE, Web of Science, Scopus, CINAHL, PsycInfo, and Cochrane Library databases to identify all fan therapy studies published from January 1, 1946 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
1
21
0
2
Order By: Relevance
“…Of these possibilities, increased temperature of the ambient air has been shown to have a larger effect than humidity on participant-reported mask comfort, with increased humidity only affecting participant-reported facemask comfort when the ambient air was above 25 C (49). Increasing facial airflow using a fan, which reduces the temperature and humidity of the air near the face, decreases dyspnea in healthy adults and those with COPD (50), suggesting that facemasks may increase dyspnea by raising facial temperature/humidity.…”
Section: Dyspneamentioning
confidence: 99%
“…Of these possibilities, increased temperature of the ambient air has been shown to have a larger effect than humidity on participant-reported mask comfort, with increased humidity only affecting participant-reported facemask comfort when the ambient air was above 25 C (49). Increasing facial airflow using a fan, which reduces the temperature and humidity of the air near the face, decreases dyspnea in healthy adults and those with COPD (50), suggesting that facemasks may increase dyspnea by raising facial temperature/humidity.…”
Section: Dyspneamentioning
confidence: 99%
“…The authors concluded limited experimental evidence of efficacy, calling for larger trials in more diverse populations and settings. 23 A secondary multimethod analysis of qualitative interview data explored benefits of a hand-held fan as perceived by patients with breathlessness (n=133, n=21 with cancer) and their carers (n=72). Most patients with usable data (91/111) perceived some or substantial benefit, described in terms of shorter recovery time, especially after physical activity.…”
Section: Non-pharmacological Symptomatic Interventionsmentioning
confidence: 99%
“…In addition, Qian et al conducted a systematic review focused on fan therapy, which included long-term and complex interventions and concluded that fan therapy may effectively alleviate dyspnea. 22 However, longterm or complex interventions interfere with direct evaluation of the efficacy of fan therapy.…”
Section: Introductionmentioning
confidence: 99%